Dissemination of antibiotic resistance genes (ARGs) via integrons in Escherichia coli: A risk to human health. (November 2020) - Zhang, Shaqiu; Abbas, Muhammad; Rehman, Mujeeb Ur; Huang, Yahui; Zhou, Rui; Gong, Siyue; Yang, Hong; Chen, Shuling; Wang, Mingshu; Cheng, Anchun
Abstract: With the induction of various emerging environmental contaminants such as antibiotic resistance genes (ARGs), environment is considered as a key indicator for the spread of antimicrobial resistance (AMR). As such, the ARGs mediated environmental pollution raises a significant public health concern worldwide. Among various genetic mechanisms that are involved in the dissemination of ARGs, integrons play a vital role in the dissemination of ARGs. Integrons are mobile genetic elements that can capture and spread ARGs among environmental settings via transmissible plasmids and transposons. Most of the ARGs are found in Gram-negative bacteria and are primarily studied for their potential role in antibiotic resistance in clinical settings. As one of the most common microorganisms, Escherichia coli ( E. coli ) is widely studied as an indicator carrying drug-resistant genes, so this article aims to provide an in-depth study on the spread of ARGs via integrons associated with E. coli outside clinical settings and highlight their potential role as environmental contaminants. It also focuses on multiple but related aspects that do facilitate environmental pollution, i.e. ARGs from animal sources, water treatment plants situated at or near animal farms, agriculture fields, wild birds and animals. We believe that this updated study with summarized text, will facilitate the readers to understand the primary mechanisms as well as a variety of factors involved in the transmission and spread of ARGs among animals, humans, and the environment. Graphical abstract: Image 1 Highlights: Various ARGs are considered as emerging environmental contaminants. Humans, animals, wastewater and manured soil and so on are possible reservoirs of ARGs in natural environment. Dissemination of ARGs via mobile elements such as integrons can play vital role in the contamination of environment. The E. coli is one of the key indicator bacteria to study AMR in diverse environments. Substantial legislative measures are required to control AMR along with intervention strategies and awareness programs.